Free Cash Flow, Capital Structure, Dividend Policy, and Stock Price - Putri, Celita Ivanda (EAJ (Economic and Accounting Journal), 2022)
This study aims to empirically prove the effect of free cash flow, capital structure, and dividend policy on stock prices. This research was conducted in a raw goods company. The type of research used is quantitative with associative methods. The data type used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (IDX) for 2017-2021. Samples were collected using a purposive sampling method. The number of companies used as research samples was ten, with research methods for 5 (five) years, so 50 observation data were obtained. The data were processed using the Eviews 12 Statistical Program to test the hypothesis using panel data regression analysis. The results of the t-statistical test on dividend policy partially have a positive effect on stock prices. However, free cash flow and capital structure partially hurt dividend policy. The results of the statistical test F free cash flow, capital structure, and dividend policy simultaneously affect stock prices.